DUKUNGAN SUAMI DENGAN KEJADIAN DEPRESI PASCA MELAHIRKAN - Tolongan, Cindritsya; Korompis, Grace E.C; Hutauruk, Minar (Universitas Sam Ratulangi, 2019)
Abstrack : Postpartum is a mother after childbirth will experience some psychological,physical or hormonal changes that can cause the mother to experience stress which cancontinue to depression, so that postpartum depression can have a negative impact on the babyand mother. The purpose of this study was to determine whether there was a relationshipbetween husband's support and the incidence of postpartum depression at the TumintingHealth Center. This research method uses a cross sectional design. The sampling techniqueused purposive sampling technique with a total sample of 50 respondents. Methods of datacollection using a husband's support questionnaire and postpartum depression in theimmunization room and maternal maternity to find out about husband's support anddepression after giving birth and statistical tests using the chi square test. The results of thestudy obtained a p-value of 0.004 (â‰¤ Î± = 0.05) which means that there is a significantdifference. The conclusion of the results of this study shows that there is a relationship thatoccurs in mothers after childbirth if there is no good husband support.Keywords: Husband support wit the incidence of postpartum depressionAbstrak : Pasca melahirkan merupakan ibu yang setelah melahirkan akan mengalamibeberapa perubahan psikologi, fisik ataupun hormonal yang menyebabkan ibu dapatmengalami stres yang dapat berlanjut hingga depresi, sehingga depresi pasca melahirkandapat berdampak buruk bagi bayi maupun ibu. Tujuan Penelitian ini adalah untukmengetahui adakah hubungan dukungan suami dengan kejadian depresi pasca melahirkan diPuskesmas Tuminting. Metode penelitian ini menggunakan desain cross sectional. Teknikpengambilan sampel menggunakan teknik purposive sampling dengan jumlah sampelsebanyak 50 responden. metode pengumpulan data menggunakan kuesioner dukungan suamidan depresi pasca melahirkan di ruangan imunisasi dan bersalin ibu untuk mengetahuidukungan suami dan depresi setelah melahirkan dan uji statistic menggunakan uji chi square.Hasil penelitian di dapat nilai p-value sebesar 0,004 (â‰¤ Î± = 0,05) yang berarti ada perbedaanyang signifikan. Kesimpulan hasil penelitian ini menunjukan bahwa ada hubungan yangterjadi pada ibu setelah melahirkan jika tidak ada dukungan suami yang baik.Kata kunci : Dukungan Suami Dengan Kejadian Depresi Pasca Melahirkan